2020
DOI: 10.1177/0363546520924011
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular Injection of Pure Platelet-Rich Plasma Is the Most Effective Treatment for Joint Pain by Modulating Synovial Inflammation and Calcitonin Gene-Related Peptide Expression in a Rat Arthritis Model

Abstract: Background: Platelet-rich plasma (PRP) has emerged as a treatment for osteoarthritis (OA). However, the effect that leukocyte concentrations in PRP have on OA remains unclear. Purpose: To clarify the optimal PRP formulation for OA treatment by comparing pure PRP, leukocyte-poor PRP (LP-PRP), and leukocyte-rich PRP (LR-PRP) in a rat arthritis model. Study Design: Controlled laboratory study. Methods: Knee arthritis was induced bilaterally in male Wistar rats with intra-articular injections of monosodium iodoace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…Another problem often associated with PRP that is the content of leukocytes in PRP. In a rat arthritis model, Araya et al [ 50 ] showed that intra-articular injection of pure PRP was the most effective treatment for inhibition of the progression of synovitis and reduction of pain. They compared pure PRP, leukocyte-pure PRP and leukocyte-rich PRP to clarify the optimal PRP formulation.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Another problem often associated with PRP that is the content of leukocytes in PRP. In a rat arthritis model, Araya et al [ 50 ] showed that intra-articular injection of pure PRP was the most effective treatment for inhibition of the progression of synovitis and reduction of pain. They compared pure PRP, leukocyte-pure PRP and leukocyte-rich PRP to clarify the optimal PRP formulation.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Very similar data were obtained in another study, where processed lipo-aspirate was injected into the rat joint after OA induction via MIA, leading to pain relief and anti-inflammatory responses [ 152 ]. Using the same OA model, another group observed a strong reduction of αCGRP-positive nerve fibers in the infrapatellar fat pad after treatment with platelet rich plasma (PRP) and associated this with the reduction of joint pain analysis of weight-bearing distribution with an incapacitance tester [ 153 ]. An increase in CGRP positive nerve fiber density was also observed in synovial tissue after MIA induced knee OA [ 154 ].…”
Section: Impact Of the Peripheral Nervous System And Its Neuropeptides On Oamentioning
confidence: 99%
“…64 Calcitonin gene-related peptide expression mediates pain reduction and down-regulation of synovial inflammation induced by PRP. 65 Advanced biomarkers, both anatomic and soluble biomarkers, reflecting several pathophysiological mechanisms, have been researched extensively, 66,67 mainly in the Osteoarthritis Research Society International (OARSI) framework, to improve OA management. 68 Accordingly, OA phenotypes were defined as 'subtypes of OA that share distinct underlying pathobiological and pain mechanisms and different course of the disease', merging in similar structural changes in final stages.…”
Section: How Work Performed In Oa Phenotyping Might Impact Prp Therapmentioning
confidence: 99%